On the National Security Correlation with Freedom of Speech in Kazakhstan - OMIRZHANOV, Yesbol; BAIMAGAMBETOVA, Zulfiya; TUSUPOVA, Almagul; OMIRTAY, Roza; UTEULIEV, Serik (Journal of Advanced Research in Law and Economics, 2017)
This article deals with problems of the relationship of national security and freedom of speech in Kazakhstan. Considering the questions about the essence and importance of national security, the authors paid special attention to the legal consolidation of the national security concept in Kazakhstan. The article also examines the theoretical foundations of the relationship of freedom of speech and national security and provides recommendations on differentiation of the definitions of national security and freedom of speech. Citing reports of reputable international organizations and materials of independent mass media, the authors considered individual cases of persecution of the freedom of expression, opposition media close-downs, harassment of independent journalists.